A case of therapy-related acute lymphoblastic leukemia following the treatment of acute myeloid leukemia. (2022) - Shikdar, Sufana; Ying, Yuan; Khawandanah, Mohamad
Abstract: Therapy-related acute lymphoblastic leukemia represents a distinct entity associated with inferior survival compared with de novo acute lymphoblastic leukemia. It consists of a subset of patients who have had exposure to chemotherapy or radiation for a previous malignancy. Here, we describe a case of acute myeloid leukemia who later developed precursor B cell acute lymphoblastic leukemia and discuss the current relevant literature. Our case highlights the importance of classifying therapy-related acute lymphoblastic leukemia as a separate as entity based on its biologic and clinical features.